EVOLUSI LEMBAGA PENDIDIKAN ISLAM DALAM SEJARAH INDONESIA - Nurul Fajri; Darul Ilmi (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this research is to explain the development of Islamic educational institutions through the challenging struggles of the Indonesian people throughout Indonesia's history. During the colonial period, the Dutch openly employed various methods to suppress Islamic education, which, at that time, took the form of Madrasah and Islamic boarding schools (pondok pesantren). This led to the emergence of a dichotomy referring to a significant division or difference between institutions of education recognized and supported by the Dutch colonial government, which tended to follow Western education systems, and traditional Islamic educational institutions such as pesantren and madrasah, which focused on Islamic education. The research method employed in this study is literature review, involving the collection of various sources on the development of Islamic educational institutions in Indonesia. The findings of this research can contribute to the literature on educational studies, particularly in the context of Islamic education. This information can serve as a reference for further research on the development of education in Indonesia. The results of the study indicate that Madrasah, as an Islamic educational institution in Indonesia, also underwent a long journey, with Dutch colonialism exerting pressure to weaken the education system in Madrasah